GENDERED LIVES, SEXUAL BEINGS : a feminist anthology. - Misra,Joya (Sage, 2018)
Contains foundational and cutting-edge articles representing a range of primary feminist research by established and early-=career scholars. The editors have carefully selected, edited, and introduced the readings with undergraduate students in mind, and the selections address many key 21st-century topics in feminist scholarship, including intersectional perspectives, global and transnational approaches, transgender, and masculinity.